Prevalence and risk factors of metabolic-associated fatty liver disease in sub-Saharan Africa: a systematic review and meta-analysis - Sindato, Emmanuel M.; Kajogoo, Violet Dismas; Ngajilo, Gloria; Degu, Wondwossen Amogne; Khan, Zahid; Mlawa, Gideon (Frontiers in Gastroenterology, 2025)
BackgroundSub-Saharan Africa (SSA) is undergoing an epidemiological transition with a steady rise in non-communicable diseases. Among these diseases, metabolic dysfunction-associated fatty liver disease (MAFLD) has emerged as a rapidly increasing public health burden, but is inaccurately documented. We characterized the MAFLD prevalence and identified associated risk factors among adults in SSA.MethodsWe searched PubMed/Medline, Cochrane, Embase, Web of Science, Google Scholar, and African Journals Online for studies looking into the prevalence of and the risk factors for MAFLD in SSA. Studies from 1990 in the English language were included, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used for reporting. The quality of the studies was assessed using the Newcastle–Ottawa Scale. A random-effects model was used to estimate the prevalence and the risk factors with 95% confidence intervals (CIs). Meta-regression was used for the subgroup analyses to account for heterogeneity. Stata version 17 software was used for the analysis. This study was registered with PROSPERO (registration no. CRD42024506067).ResultsA total of 538 studies were identified, with 22 included in the analysis. The overall prevalence of MAFLD was 29·21% (95%CI = 22.09–36.88, p < 0.05). Regionally, the results were: West, 34.36%; South, 26.92%; and East, 24.56%. The prevalence of MAFLD among people living with HIV was 13.02%, with diabetes was 37.06%, with hypertension was 36.75%, and with a body mass index above 25 kg/m2 was 46.05%. The prevalence was higher in women than in men (27.13% vs. 23.01%), as shown in studies conducted from 2000 onwards compared with those conducted between 2009 and 2019 (30.23% vs. 28.4%) and in studies with small sample sizes <500 than in studies with large sample sizes >500 (32.42% vs. 12.17%).InterpretationMAFLD is highly prevalent in SSA, with a steady increasing magnitude. The significant risk factors included diabetes, hypertension, obesity, and female sex. This study underscores the emerging need of clinicians in SSA to screen MAFLD among patients at high risk and to instigate tailored care.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024506067.